Endosperm genotyping as a strategy to differentiate the allele source in maize heterozygous progeny - Martins, Francielle Alline; Carneiro, Pedro Crescêncio Souza; Cruz, Cosme Damião; Carneiro, José Eustáquio de Souza; Guimarães, Claudia Teixeira (Pesquisa Agropecuaria Brasileira, 2010)
The objective of this work was to distinguish the parental source of alleles in heterozygous progeny using semiquantitative polymerase chain reaction (PCR) in maize endosperm. Endosperms derived from direct and reciprocal single-cross hybrids between maize inbred lines L3 and L1113-01 were genotyped by semiquantitative PCR methodology (SQ-PCR) using fluorescent microsatellite primers. The amplification products were evaluated by the ratios of fluorescence intensity (RFI), calculated between the peaks corresponding to the alleles derived from each parental line. Based on the statistically significant contrast between RFI mean values of direct and reciprocal single-cross hybrids, it was possible to distinguish the number of alleles received from each parental line and, ultimately, to determine the origin of the alleles of each cross. Thus, endosperm genotyping using SQ-PCR is a promising strategy to map QTL in maize outbred populations.
Keywords: Zea mays; allelic origin; heterozygote; natural populations; polygenes; semiquantitative PCR